Функциональный анализ профессиональной подготовки будущих учителей музыки - Бондаренко, Дмитро Володимирович (Pedagogy of Higher and Secondary Education, 2017)
The article examines pedagogical functionіs as basic components of professional training of future music teachers at institutes of arts and musicalpedagogical faculties of pedagogical universities during the choral conductorforming adaptive teaching. The purpose of the article is to study the teaching functions in the process of training future music teachers in higher education institutions. Formation of adaptive readiness of future teachers of music for choral conductors is an important stage of their training. The peculiaries of adaptiness of music teachers to the conditions of pedagogical work based on a psycho-pedagogical concept, which ipmply the necessity to take into account the featof teaures of teaching music teacher for work in secondary schools, as well as laws and choral conductors. Acquired competence of future music teachers in higher education establishments directly relates to their adaptive readiness to perform professional activities. We have singled out the basic functions of training students of the Institute of Arts and Music and the Faculty of Education in Pedagogical Universities in the course of conducting and choral studies, namely, system-integrated, cognitive orientation, operational and regulatory, suggestively-training, predictive-correction. The function of training system-integrated specialists is to organize training teachers of students in the study cycle conducting and choral disciplines in universities. Cognitive-orientation features imply the outlook for future music teachers, which is the basis of their practical-cognitive self-employment. Operational and regulatory function of preparation of experts is to organize educational activities aimed at students’ formation their adaptive readiness for conducting and choral activities. Suggested developing functions are directed for the use of possibilities of teachers to make a positive influence on the professional development of students. Corrective, predictive function helps to create effective conditions for teaching forms, methods and tools for the adaptation of students to study choral conductor-like activity aimed at fulfilling their educational potential, social activity and professional development. This compensation is impossible without less developed functions and complementarities.